Expression of Professional Motivation for Choosing Social-Educational Work: Transcultural Comparison - Urbonienė, Aistė; Leliūgienė, Irena (Acta Paedagogica Vilnensia, 2004)
The importance of professional motivation in the process of choosing social-educational work is analysed, stressing the exception of social work as occupation in the context of dynamic society. The article presents the concept of professional motivation. The influence of personal and socio-cultural factors on the formation of the professional motivation is analysed and the structural model is presented. Results of the transcultural research on professional motivation are presented and some tendencies of motives why people choose social-educational work as occupation in Byelorussia, Lithuania and Sweden are discussed. The statistical analysis of data illuminated dependence of professional motives’ from the socio-cultural factors in choosing university studies in social-educational profession. The results indicated that Byelorussia students expressed a disposition to human-oriented goals, in Swedish sample here is a greater dominance there of external achievements that are typical for the modern Western society and in Lithuanian sample here is no significant difference there between human-oriented and self-realization goals what can be explained as a sign of value-shift in the changing society.